2020
DOI: 10.1371/journal.pone.0232265
|View full text |Cite
|
Sign up to set email alerts
|

Distinct bacterial communities in tropical island aquifers

Abstract: The groundwater biome is a poorly characterized habitat hypothesized to harbor uniquely diverse bacterial communities; the degree to which these communities differ from associated soils is a central question in environmental microbiology. We characterized the Bacterial community composition in 37 aquifer and 32 surface soil samples across the island of O'ahu, Hawai'i. Several bacterial phyla (Acetothermia, Omnitrophica, Parcubacteria, Peregrinibacteria) relatively abundant in the aquifer samples were rare to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…These results suggested that potassium was the most important factor affecting bacterial community in Bombax -rice agroforestry system. Similarly, a study in tropical island aquifers con rmed that potassium had most signi cant relationship with bacterial community (Kirs et al 2020).…”
Section: Discussionmentioning
confidence: 90%
“…These results suggested that potassium was the most important factor affecting bacterial community in Bombax -rice agroforestry system. Similarly, a study in tropical island aquifers con rmed that potassium had most signi cant relationship with bacterial community (Kirs et al 2020).…”
Section: Discussionmentioning
confidence: 90%
“…There has been little prior characterization of the biota of Hawai'i groundwater, although one recent study has documented diverse bacterial communities on Oahu to the phylum or class level (Kirs et al., 2020). They noted that Actinobacteria , the phylum to which NTM belong, are present in nearly all groundwater, albeit at a relatively low mean abundance (2.2%) but are a major constituent (26%) of the soil biome.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, mycobacteria are a significant, if minor component of Hawai'i aquifer and a major component of soil biomes (Kirs et al., 2020), and cell count and transport studies indicate up to >10 7 cells/ml of bacteria may be expected in fractured basalt. NTM are now known to exist in the riparian environments of Kauai and Oahu where cells may tend to bind with hematite (Glickman et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Large subsurface aquatic habitats, like the volcanic groundwater aquifers of Hawaiʻi, support diverse communities due to the unique microenvironments available (e.g., surfaces, biofilms, particles) providing various and overlapping redox potentials (Bethke et al., 2011; Seitzinger et al., 2006). The most common metabolic pathways in groundwater ecosystems are chemolithoautotrophic, often utilizing hydrogen (H), S, Fe, and manganese (Mn) with oxygen (O) and nitrate (NO 3 ) as the most widely used electron acceptors (Anantharaman et al., 2016; Kirs et al., 2020). On volcanic islands, S compounds are often contaminants in freshwater as sulfate (SO42$$ {\mathrm{SO}}_4^{2-} $$), sulfides (S 2− ), polysulfides (SxO62$$ {\mathrm{S}}_x{\mathrm{O}}_6^{2-} $$), and thiosulfate (S2O32$$ {\mathrm{S}}_2{\mathrm{O}}_3^{2-} $$), sourced from geothermal activity or seawater inputs (Flynn et al., 2012; Stefánsson et al., 2011; Xu et al., 1998).…”
Section: Introductionmentioning
confidence: 99%